The cultural studies reader - During, Simon (Routledge, 1999)
The first edition of <The Cultural Studies Reader> established itself as the leading textbook in the field, providing the ideal introduction for students to this exciting and influential discipline. This expanded second edition offers: * 38 essays including 18 new articles * an editor's preface succinctly introducing each article * comprehensive coverage of every major cultural studies method and theory * an updated account of recent changes in the field * articles on new areas such as science and cyberculture, globalization, postcolonialism, public spheres and cultural policy * a fully revised introduction and an extensive guide to further reading.